2007
DOI: 10.1095/biolreprod.106.056127
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotrophoblast Layer of Human Chorionic Villi Becomes Thinner but Maintains Its Structural Integrity During Gestation1

Abstract: Chorionic villi in the human placenta serve as essential structures in fetomaternal exchanges. According to the embryology and placentology literature, during the first trimester, the cytotrophoblast (CTB) layer that is subjacent to the syncytiotrophoblast (STB) and supported by a basal lamina is nearly complete, but later, it becomes discontinuous. In the present study, we investigated the structural integrity of the CTB layer in the normal villous tree by advanced microscopy techniques using an antibody to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 39 publications
3
26
0
2
Order By: Relevance
“…Such damage might occur in the presence of a second infectious agent or due to physical trauma. The effects may also depend on the placenta's gestational age, as the layer of subsyncytial cytotrophoblasts undergirding the syncytiotrophoblast grows thinner and partially discontinuous after the first trimester (37,50).…”
Section: Discussionmentioning
confidence: 99%
“…Such damage might occur in the presence of a second infectious agent or due to physical trauma. The effects may also depend on the placenta's gestational age, as the layer of subsyncytial cytotrophoblasts undergirding the syncytiotrophoblast grows thinner and partially discontinuous after the first trimester (37,50).…”
Section: Discussionmentioning
confidence: 99%
“…LOX-1 staining in Figure 3 of their report (Lee et al 2005), however, seems to localize in the cytotrophoblast layer. In a recent study, Mori et al (2007) reported that the cytotrophoblast layer in the term placenta becomes thinner by spreading their cell surface over the basal lamina, and 80% of its continuity is still preserved. Our data of LOX-1 localization in term placenta support their observation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, it was proposed by Mori et al that the cytotrophoblast layer of chorion villi becomes thinner during gestation, resulting in a gradual over-representation of the mesenchymal lineage. 17 Since in case 1 we found that the CVS in the 21 st week of gestation displayed MLPA results representative of the cytotrophoblast lineage, we could not confirm this latter notion.…”
Section: Discussionmentioning
confidence: 73%